The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4250/jcvi.2021.0170
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Interventricular Septum Volume Evaluated by Three-Dimensional Ultrasound Using Spatiotemporal Image Correlation and Virtual Organ Computer-Aided Analysis in Fetuses From Pre-Gestational Diabetes Mellitus Pregnant Women

Abstract: BACKGROUND To assess the interventricular septum (IVS) volume of fetuses from pre-gestational diabetes mellitus (DM) pregnant women by 3-dimensional ultrasound using spatiotemporal image correlation (STIC) and virtual organ computer-aided analysis (VOCAL) methods. METHODS This was a prospective cross-sectional study of 45 fetuses from pre-gestational DM and 45 fetuses from healthy pregnant women (controls). Only singleton pregnancies between 20 and 34 + 6 weeks of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…5 Several studies have shown that GDM is significantly associated with both morphological and functional changes in the fetal heart. [6][7][8][9][10] Though the true mechanism is still unclear, it has been demonstrated that fetal cardiac changes are partly caused by fetal hyperglycemia and hyperinsulinemia, which triggers fat and protein synthesis in myocardial cells. 11,12 Fetal myocardial changes may be observed in even cases with wellcontrolled GDM.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies have shown that GDM is significantly associated with both morphological and functional changes in the fetal heart. [6][7][8][9][10] Though the true mechanism is still unclear, it has been demonstrated that fetal cardiac changes are partly caused by fetal hyperglycemia and hyperinsulinemia, which triggers fat and protein synthesis in myocardial cells. 11,12 Fetal myocardial changes may be observed in even cases with wellcontrolled GDM.…”
Section: Introductionmentioning
confidence: 99%
“… 19) 20) Bravo-Valenzuela et al 21) reported significantly smaller fetal left atrial volume in fetuses from pregestational DM women than healthy mothers. Melo Júnior et al 20) reported no significant difference in mean fetal myocardial volume between normal pregnant women and those with pregestational diabetes, whereas Edward Bravo-Valenzuela et al 22) showed the significantly higher fetal IVS volumes by 3D ultrasound with STIC with VOCAL methods in pregestational DM mothers than healthy mothers.…”
mentioning
confidence: 98%